Plan de negocios para la insdusrialización y exportación de lúcuma de seda - Álvarez Huamani, Zoila (2006)
The authors evaluate the best alternatives to offer eggfruit in foreign markets, by stressing the fruit’s advantages and looking for an appropriate by-product attractive for exportation. Their evaluation is based on a research on eggfruit, its types, characteristics, uses, growing in Peru and industrialization methods, and also on statistical data collection, and production and exports projections. Italy was found to be the most appropriate destination, because of its traditional ice cream market, where freeze-dried eggfruit powder can be used as main fl avoring input. Taking these fi ndings into account, the authors propose a 10-year business plan which includes a strategic proposal for installation and business growth, both at the production integration level and the product development level. It is about the search for a feasible, profi table and sustainable business opportunity